Vitamin D3 Suppresses Class II Invariant Chain Peptide Expression on Activated B-Lymphocytes: A Plausible Mechanism for Downregulation of Acute Inflammatory Conditions - Omar K. Danner; Leslie R. Matthews; Sharon Francis; Veena N. Rao; Cassie P. Harvey; Richard P. Tobin; Ken L. Wilson; Ernest Alema-Mensah; M. Karen Newell Rogers; Ed W. Childs (Journal of Nutrition and Metabolism)
Class II invariant chain peptide (CLIP) expression has been demonstrated to play a pivotal role in the regulation of B cell function after nonspecific polyclonal expansion. Several studies have shown vitamin D3 helps regulate the immune response. We hypothesized that activated vitamin D3 suppresses CLIP expression on activated B-cells after nonspecific activation or priming of C57BL/6 mice with CpG. This study showed activated vitamin D3 actively reduced CLIP expression and decreased the number of CLIP+ B-lymphocytes in a dose and formulation dependent fashion. Flow cytometry was used to analyze changes in mean fluorescent intensity (MFI) based on changes in concentration of CLIP on activated B-lymphocytes after treatment with the various formulations of vitamin D3. The human formulation of activated vitamin D (calcitriol) had the most dramatic reduction in CLIP density at an MFI of 257.3 [baseline of 701.1 (P value = 0.01)]. Cholecalciferol and alfacalcidiol had no significant reduction in MFI at 667.7 and 743.0, respectively. Calcitriol seemed to best reduce CLIP overexpression in this ex vivo model. Bioactive vitamin D3 may be an effective compliment to other B cell suppression therapeutics to augment downregulation of nonspecific inflammation associated with many autoimmune disorders. Further study is necessary to confirm these findings.